2014
DOI: 10.1155/2014/921564
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Regulation of E-Cadherin by Zinc Finger E-Box Binding Homeobox Proteins in Solid Tumors

Abstract: Downregulation of E-cadherin in solid tumors with regional migration and systematic metastasis is well recognized. In view of its significance in tumorigenesis and solid cancer progression, studies on the regulatory mechanisms are important for the development of target treatment and prediction of clinical behavior for cancer patients. The vertebrate zinc finger E-box binding homeobox (ZEB) protein family comprises 2 major members: ZEB1 and ZEB2. Both contain the motif for specific binding to multiple enhancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 124 publications
3
74
0
2
Order By: Relevance
“…In human and murine cancer models, it was already demonstrated that ZEB1 and ZEB2 can downregulate epithelial markers such as E‐cadherin and cytokeratin . Our results support this result as we found an inverse correlation among ZEB transcription factors and E‐cadherin expression in the CMC cell lines.…”
Section: Discussionsupporting
confidence: 89%
“…In human and murine cancer models, it was already demonstrated that ZEB1 and ZEB2 can downregulate epithelial markers such as E‐cadherin and cytokeratin . Our results support this result as we found an inverse correlation among ZEB transcription factors and E‐cadherin expression in the CMC cell lines.…”
Section: Discussionsupporting
confidence: 89%
“…ZEB2, an E-box-binding transcription factor, was involved in the tumorigenesis of various malignancies 31. Moreover, ZEB2 was reported to promote tumor cell invasion and metastasis as it could directly bind the E-cadherin promoter and strongly inhibit E-cadherin expression during EMT 32. Here, we found that knockdown of SOX2OT significantly decreased ZEB2 expression on mRNA and protein levels, whereas co-transfection with sh-SOX2OT and miR-132 inhibitor increased ZEB2 expression levels in both A549 and H1299 cells.…”
Section: Discussionmentioning
confidence: 99%
“…E-cadherin is a tumor suppressor that mediates cell-cell adhesion and cell-extracellular matrix interactions (19). Li et al (20) revealed that the downregulation of AQP4 results in increased expression of E-cadherin in breast cancer cells, although the association between AQP9 and E-cadherin expression is unclear.…”
Section: Discussionmentioning
confidence: 99%